2015
DOI: 10.1097/ico.0000000000000562
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 Randomized Double-Masked Study of Efficacy and Safety of Once-Daily 0.77% Olopatadine Hydrochloride Ophthalmic Solution in Subjects With Allergic Conjunctivitis Using the Conjunctival Allergen Challenge Model

Abstract: Olopatadine 0.77% demonstrated a rapid onset and prolonged duration of action. It was superior to all comparators in alleviating AC-associated ocular itching with a favorable safety profile.Clinical Trial Registration-URL: http://www.clinicaltrials.gov. Unique identifier: NCT01743027.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 17 publications
3
28
0
Order By: Relevance
“…The new ophthalmic formulation of olopatadine at an increased concentration of 0.77% was developed with the aim to increase the aqueous solubility of olopatadine at neutral pH and to provide better efficacy in the management of ocular allergy compared with the previously approved olopatadine ophthalmic formulations (0.1% and 0.2%). Superior efficacy of olopatadine 0.77% over 0.1% and 0.2% formulations was recently shown in Phase III clinical trials 14,15. In a pre-clinical study, olopatadine 0.77% formulation showed improved solubility and a 4-fold increase in the concentration of olopatadine in the aqueous humor when compared to olopatadine 0.2%, with no sign of capacity-limit kinetics 16.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The new ophthalmic formulation of olopatadine at an increased concentration of 0.77% was developed with the aim to increase the aqueous solubility of olopatadine at neutral pH and to provide better efficacy in the management of ocular allergy compared with the previously approved olopatadine ophthalmic formulations (0.1% and 0.2%). Superior efficacy of olopatadine 0.77% over 0.1% and 0.2% formulations was recently shown in Phase III clinical trials 14,15. In a pre-clinical study, olopatadine 0.77% formulation showed improved solubility and a 4-fold increase in the concentration of olopatadine in the aqueous humor when compared to olopatadine 0.2%, with no sign of capacity-limit kinetics 16.…”
Section: Discussionmentioning
confidence: 93%
“…In a preclinical study, olopatadine was observed at higher concentrations with prolonged presence in the target tissue (rabbit conjunctiva) following dosing with olopatadine 0.77% compared to that with olopatadine 0.2% 16. The new olopatadine 0.77% formulation has demonstrated a longer, 24-hour duration of action and superior efficacy compared to olopatadine 0.2% formulation in Phase III clinical studies 14,15. This new formulation of olopatadine 0.77% (marketed as PAZEO ® by Alcon Research Ltd.) was approved by the US Food and Drug Administration (FDA) in 2015 as once-daily product for the treatment of ocular itching associated with allergic conjunctivitis.…”
Section: Introductionmentioning
confidence: 99%
“…53 At 3, 5, and 7 minutes after CAC, ocular itch reduction with olopatadine 0.77% was superior to vehicle at onset and 24 hours after instillation (Fig. 3 A ) and to active control formulations 24 hours after instillation (Fig.…”
Section: Benefits Of a True 24-hour Topical Medicationmentioning
confidence: 89%
“…In both studies, adverse events and other safety parameters were similar across treatment groups, and the safety profile of olopatadine 0.77% was similar to that of olopatadine 0.2%. 52,53 Together, these trials indicate that olopatadine 0.77% is more effective and maintains a longer duration of action compared with currently available olopatadine formulations and that once-daily olopatadine 0.77% provides an effective 24-hour control of AC signs and symptoms.…”
Section: Benefits Of a True 24-hour Topical Medicationmentioning
confidence: 93%
See 1 more Smart Citation